Pengaruh Digitalisasi Akuntansi terhadap Efisiensi dan Pengurangan Biaya pada Perusahaan Wirausaha UMKM di Kota Makassar - Sriningsih, Endang; Syam, Nur Azisah; Mustamin, Icha (Jurnal Penelitian Multidisiplin Ilmu, 2025)
This study aims to examine and analyze the impact of accounting digitalization on operational efficiency and cost reduction in MSME entrepreneurial firms in Makassar City. A quantitative method was employed, with data collected through questionnaires distributed to 100 MSMEs in the city. The collected data were analyzed using statistical software to assess the relationship between the variables: accounting digitalization, operational efficiency, and cost reduction. The findings reveal that (1) accounting digitalization significantly influences the operational efficiency of MSMEs; and (2) accounting digitalization also significantly impacts cost reduction in MSMEs' operations. These results indicate that implementing digital accounting systems can help MSMEs enhance operational effectiveness and reduce costs, which are crucial for their competitiveness and business sustainability. This study contributes to (1) the development of knowledge in the field of digital accounting and offers practical insights for MSMEs to leverage technology in optimizing their financial processes; (2) providing a basis for government policies or programs aimed at supporting the digital transformation of MSMEs, particularly in the accounting sector; and (3) improving performance and competitiveness in an increasingly competitive market.